Fiscal Deficit and Taxes in India: Some Observations - T. Parmar, Mitulkumar (Management Journal for Advanced Research, 2023)
The national and international evidences suggest that the government projects, and production activities have not been producing considerable returns and profits even to take care of opportunity costs. The attempt in this study is not to focus analytically into public expenditure but delve into some of the important elements and considerations which shaped policy concerns for taxation and their subsequent implications on fiscal deficits and borrowings. Considering the nature of exposition organised in this study, an exploratory analysis is adopted from the viewpoints of expressing critical opinions which are based on existing information and overall fiscal scenario by taking into account of inflation, financial markets, public debt management and economic growth. The behaviour of centre’s direct tax has direct impact on trend of the combined direct tax, but evidently indirect tax of the centre has not produced any significant impact on combined indirect tax due to the fact states’ indirect taxes have been reasonably and strongly stable even when economic growth rate slipped during COVID-19. Gross Fiscal Deficit and revenue deficit are moving in tandem, and this importantly means unless a significant decrease in revenue expenditures is brought down in the form of decline in the current expenditure, the fiscal prudency in bringing the fiscal deficit below the three percent of Gross Domestic Products (GDP) is extremely difficult exercise. The market borrowing as a critical and pre-dominant source of deficit financing has created dynamic changes in both money markets and capital markets. Along with financial deepening, integration of government securities and treasury bills play an important role in deciding particularly short-term financial rates by giving greater substitutability and greater return with almost no risk. The scenario narrated on taxes and borrowing could well produce some mixed implications for macro management and financial sectors. Government should look forward for correcting their fiscal course at least in terms of bringing fiscal deficit closer to the sustainable level while making taxes to strengthen market mechanism.